Excisional treatments of the cervix and effect on subsequent fertility: a retrospective cohort study. (February 2015) - Martyn, Fiona M.; McAuliffe, Fionnuala M.; Beggan, Caitlin; Downey, Paul; Flannelly, Grainne; Wingfield, Mary B.
Abstract: Objective: Concerns exist regarding the impact of excisional treatments for cervical intraepithelial neoplasia (CIN) on subsequent pregnancy outcome yet few studies have addressed fertility following surgery. Study design: Retrospective cohort study. Set in the colposcopy service of National Maternity Hospital. A postal questionnaire was sent to 3590 women of reproductive age who attended colposcopy from 2001 to 2007; 1795 of these had at least one excisional treatment (surgical group) and 1795 had no treatment (non-surgical group). Records were reviewed to confirm the clinical details and volume of tissue excised. The main outcome measures were pregnancy and fertility rates as well as time to conception correlated with volume of tissue excised. Students' t -test, Mann–Whitney U -test, spearman correlation and Kruskal–Wallis tests were used during the analysis. Results: 1355 Women (37.7%) responded. 537 Women had no treatment and 818 had at least one excision. A subsequent pregnancy was reported in 730 women (434 surgical and 296 non-surgical groups). No difference was detected between the groups in the reported pregnancy rates ( p  = 0.56), the time to conception ( p  = 0.37) or fertility problems ( p  = 0.89). The volume of the excision did not affect fertility rates or time to conception. There were fewer pregnancies in women following a cold knife cone or more than one LLETZ treatment-significant surgery, ( p  = 0.004) but no difference in their reported time to conception ( p  = 0.54). Conclusions: One excisional treatment for CIN does not appear to affect subsequent fertility. Our study showed no delay in conception and no increased risk of problems conceiving in this group, even when controlling for the volume and depth of tissue removed. Women should be reassured by these results. Further work is required to evaluate the effect of cold knife cone biopsy and repeated LLETZ procedures on subsequent fertility.